Outcomes of bone marrow mononuclear cell transplantation combined with interventional education for autism spectrum disorder - Nguyen Thanh, Liem (Stem Cells Transl Med, 2020)
The aim of this study was to evaluate the safety and efficacy of autologous bone marrow mononuclear cell transplantation combined with educational intervention for children with autism spectrum disorder. An open‐label clinical trial was performed from July 2017 to August 2019 at Vinmec International Hospital, Hanoi, Vietnam. Thirty children who fulfilled the autism criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, and had Childhood Autism Rating Scale (CARS) scores >37 were selected. Bone marrow was harvested by anterior iliac crest puncture under general anesthesia. The volume collected was as follows: 8 mL/kg for patients under 10 kg (80 mL + [body weight in kg − 10] × 7 mL) for patients above 10 kg. Mononuclear cells were isolated with a Ficoll gradient and then infused intrathecally. The same procedure was repeated 6 months later. After the first transplantation, all patients underwent 8 weeks of educational intervention based on the Early Start Denver Model. There were no severe adverse events associated with transplantation. The severity of autism spectrum disorder (ASD) was significantly reduced, with the median CARS score decreasing from 50 (range 40‐55.5) to 46.5 (range 33.5‐53.5) (P < .05). Adaptive capacity increased, with the median Vineland Adaptive Behavior Scales score rising from 53.5 to 60.5. Social communication, language, and daily skills improved markedly within 18 months after transplantation. Conversely, repetitive behaviors and hyperactivity decreased remarkably. Autologous bone marrow mononuclear cell transplantation in combination with behavioral intervention was safe and well tolerated in children with ASD (Trial registration: ClinicalTrials.gov identifier: NCT03225651).